2017
DOI: 10.4081/ripppo.2017.227
|View full text |Cite
|
Sign up to set email alerts
|

The Italian version of the Depressive Experiences Questionnaire: psychometric properties and validation in students, community, and clinical groups

Abstract: The current study evaluated the psychometric properties of the Italian validation of the Depressive Experiences Questionnaire (DEQ), conceived as a measure of self-criticism and dependency, i.e. two personality factors acting, according to Blatt (2004), as risk factors for depression in particular and psychopathology in general. A series of standardized measures [Beck Depression Inventory-II (BDI-II), DEQ, Symptom Checklist-90-R (SCL-90-R), Millon Clinical Multiaxial Inventory, 3rd edition (MCMI-III)] was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Dependence and relatedness were scored using the scoring method of Blatt et al (1995) by summing the items contained in the subscales (respectively, 10 and 8 items). The Italian version of the DEQ has good internal consistency and validity, similar to those of the original DEQ ( Falgares et al, 2017b ). In the present study, reliability as measured with the Cronbach’s α was 0.83 for self-criticism, 0.72 for dependence, and 0.79 for relatedness.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…Dependence and relatedness were scored using the scoring method of Blatt et al (1995) by summing the items contained in the subscales (respectively, 10 and 8 items). The Italian version of the DEQ has good internal consistency and validity, similar to those of the original DEQ ( Falgares et al, 2017b ). In the present study, reliability as measured with the Cronbach’s α was 0.83 for self-criticism, 0.72 for dependence, and 0.79 for relatedness.…”
Section: Methodsmentioning
confidence: 66%
“…The 66-item self-report Italian version of the DEQ ( Blatt et al, 1976 ; Falgares et al, 2017b ) was used to assess pathological personality traits. Despite its name, the DEQ measures stable personality traits which confer risk for the development of depression, but which do not measure acute depression ( Mongrain and Zuroff, 1994 ; Zuroff et al, 2004 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on this total score, severity of depressive symptoms is ranked into four levels: 0–13 (minimal depressive symptoms), 14–19 (mild depressive symptoms), 20–28 (moderate depressive symptoms) and 29–63 (severe depressive symptoms). The Italian version of the BDI-II used in this study has shown high internal consistency (Cronbach α =0.80), good convergent validity with the Depression Questionnaire ( 11 ), and good test-retest reliability after 1 month ( r = 0.76) ( 12 ).…”
Section: Methodsmentioning
confidence: 98%
“…The Italian version of the Depressive Experiences Questionnaire (DEQ; Blatt, Schaffer, Bers, & Quinlan, 1992; Falgares et al, 2017) adapted for adolescents was used to measure self-criticism and dependency. The DEQ consists of 66 self-reported items yielding factor scores for three primary factors: dependency, self-criticism, and efficacy.…”
Section: Methodsmentioning
confidence: 99%